Pengembangan Model Manajemen Risiko Terintegrasi untuk Inovasi Digital Perbankan Syariah - Gusti Oka Widana; Waliyudin (Jurnal Ilmiah Ekonomi Islam, 2025)
This study aims to formulate and propose a comprehensive, integrated risk management model to address the challenges of digital innovation in Islamic banking. This research is motivated by the emergence of hybrid risk profiles and a significant governance gap resulting from siloed risk management practices among the IT Division, the Risk Management Division, and the Sharia Supervisory Board (DPS). This study employs a descriptive qualitative method using a library research approach. Data was collected through a documentary analysis of existing literature, encompassing scientific journals, industry standards (COSO ERM, COBIT), Sharia standards (AAOIFI, DSN-MUI Fatwas), and banking regulations (POJK). Data analysis was conducted via critical synthesis, focusing on gap analysis within existing frameworks to construct a new conceptual model. The finding of this study is the "Integrated Sharia Digital Risk Management" (MR-DST) model. This model is built on three main pillars: (1) Integrated Governance, which integrates the role of the DPS into the technology development lifecycle and the IT risk committee; (2) Holistic Risk Assessment Process, which combines Technology Risk Assessment (TRA) and Sharia Compliance Risk Assessment (SCRA) from the product ideation phase; and (3) Cross-Functional Human Resource Capacity, which emphasizes digital literacy for the DPS and Sharia literacy for the IT team. This model offers a proactive framework through a synthesis between the IT risk framework (COBIT) and Sharia governance frameworks (AAOIFI/DSN-MUI).